2011
DOI: 10.2337/db10-1080
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance Impairs Circulating Angiogenic Progenitor Cell Function and Delays Endothelial Regeneration

Abstract: OBJECTIVECirculating angiogenic progenitor cells (APCs) participate in endothelial repair after arterial injury. Type 2 diabetes is associated with fewer circulating APCs, APC dysfunction, and impaired endothelial repair. We set out to determine whether insulin resistance adversely affects APCs and endothelial regeneration.RESEARCH DESIGN AND METHODSWe quantified APCs and assessed APC mobilization and function in mice hemizygous for knockout of the insulin receptor (IRKO) and wild-type (WT) littermate controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 53 publications
5
52
1
Order By: Relevance
“…This observation contrasts with our recent findings in mice with haploinsufficiency of the insulin receptor in which endothelial regeneration was compromised 4 and implies divergent functional consequences of downregulation of the 2 tyrosine kinase receptors on vascular repair. We did not uncover any differences in angiogenic sprouting between vessels from IGF1R +/− and WT mice in vitro, suggesting that alterations in circulating progenitor cells rather than native endothelial cells likely contributed to the enhanced endothelial regeneration observed in vivo.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…This observation contrasts with our recent findings in mice with haploinsufficiency of the insulin receptor in which endothelial regeneration was compromised 4 and implies divergent functional consequences of downregulation of the 2 tyrosine kinase receptors on vascular repair. We did not uncover any differences in angiogenic sprouting between vessels from IGF1R +/− and WT mice in vitro, suggesting that alterations in circulating progenitor cells rather than native endothelial cells likely contributed to the enhanced endothelial regeneration observed in vivo.…”
Section: Discussioncontrasting
confidence: 56%
“…4 Splenectomized WT mice were infused with WT or IGF1R +/− bone marrow-derived CD117 + (c-kit + ) cells or saline after femoral artery injury. Re-endothelialization was significantly enhanced by infusion of IGF1R +/− CD117 + bone marrow-derived cells when compared with infusion of WT cells or cell-free saline ( Figure 5A and 5B).…”
Section: Effect Of Partial Deletion Of Igf1r In Transfused Cd117 + Cementioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it was also reported that after arterial injury in hemizygous knockout mice for the insulin receptor (IRKO), EPCs activities were altered and endothelial regeneration delayed. This defective endothelial repair could be normalized by transfusion of progenitor cells from insulin-sensitive animals, but not from insulin-resistant animals (Kahn et al, 2011). However, it is thought that EPCs biological modifications are mostly affected by IR in an indirect fashion, through the increase in ROS and also by the activation of pro-inflammatory cytokines (Cubbon et al, 2007;2009;Houstis et al, 2006).…”
Section: Insulin Resistance (Ir)mentioning
confidence: 99%